2019
DOI: 10.31185/ejuow.vol7.iss1.113
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effect of interrupted fin arrangements on the Thermal Performance of a Heat Sink under a Free Convection Condition

Abstract: The heat sink with vertically rectangular interrupted fins was investigated numerically in a natural convection field, with steady-state heat transfer. A numerical study has been conducted using ANSYS Fluent software (R16.1) in order to develop a 3-D numerical model.  The dimensions of the fins are (305 mm length, 100 mm width, 17 mm height, and 9.5 mm space between fins. The number of fins used on the surface is eight. In this study, the heat input was used as follows: 20, 40, 60, 80, 100, and 120 wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Mostafavi et al 22 investigated the effects of adding interrupted fins to a rectangular vertically mounted heat sink and observed that it enhanced the thermal performance accompanied by reduced weight and manufacturing costs. Jubear et al 23 studied the effects of different interrupted fin arrangements and orientation on enhancing the thermal performance of a heat sink and the results showed that it indeed had an effect on the thermal performance. Chavan et al 24 also studied the effects of fin spacing, interruption, and perforation on the thermal performance of a heat sink in different interrupted fin arrangements like inline and staggered.…”
Section: Introductionmentioning
confidence: 99%
“…Mostafavi et al 22 investigated the effects of adding interrupted fins to a rectangular vertically mounted heat sink and observed that it enhanced the thermal performance accompanied by reduced weight and manufacturing costs. Jubear et al 23 studied the effects of different interrupted fin arrangements and orientation on enhancing the thermal performance of a heat sink and the results showed that it indeed had an effect on the thermal performance. Chavan et al 24 also studied the effects of fin spacing, interruption, and perforation on the thermal performance of a heat sink in different interrupted fin arrangements like inline and staggered.…”
Section: Introductionmentioning
confidence: 99%